Perspectivas e desafios da formação docente em geografia: uma análise da formação no PIBID/ UEPB - Pontes, Robson Sales (2019)
Identifying the formative perspectives from the experiences of the subproject of Geography of the Pibid / UEPB in the formation of the professor of Geography was the object of research of this dissertation of professional masters. The use of pedagogical materials, prepared for the teaching of Geography in the school of basic education, with emphasis on the didactic sequence, was the starting point for the elaboration of the master's product. The research was conducted using a theoretical-methodological approach, the case study of the production of the Pibid Geography subproject / UEPB - campus I, identifying the way in which the program promotes the training of future teachers. The questions that guided the research stages were: What are the challenges of articulating theory and practice in the formation of the future professor of Geography ?; How does the training of graduates take place through participation in a fellowship program?; How do the graduates of the program analyze their teaching practice? The stages of the research consisted of analysis of the production of the Geography subproject through reports, bibliographic review and questionnaire for graduates of the subproject. The analysis of the productions through the reports showed how the production of specific materials for the teaching of Geography subsidized good practices for teachers of basic education. The bibliographic review was based on authors such as Imbernón (2009) that deals with the permanent formation of teachers; Zeichner (2009), which addresses aspects of research in teacher education; Oliveira (2009) and Rego (1987) on teacher training in Geography: Sacristán (2006) and Tardiff (2002) deal with teaching knowledge and professional experience; Castellar (2010), Callai (2010), explain about the initial formation in Geography. In a complementary way, through the questionnaire it was possible to access the perspective of graduates regarding the contributions of the program to the teaching practice, now as teachers. In general terms, with the accomplishment of this research it was possible to identify the way in which the participation in the Pibid makes possible a future practice more educated and collaborative between the university and the school of basic education.